(untitled) (REMUNOM, 2024)
Introduction: Pregnancy is characterized by several physiological changes that can produce uncomfortable symptoms. To alleviate certain discomforts, pregnant women often use medications without knowing the possible risks to their own health and fetal development. Exposure to some medications can cause serious outcomes, such as miscarriage and congenital malformations, especially in the first trimester of pregnancy. Objective: to analyze the role of pharmacists in providing guidance to pregnant women on medication consumption. Method: integrative literature review, with searches carried out in the Scientific Electronic Library Online (SciELO); Latin American and Caribbean Literature in Health Sciences (LILACS); and the PubMed Central (PMC) search engine, as well as through complementary searches through the Google Scholar website. Only studies published between 2019 and 2023, in Portuguese or English, with at least one of the descriptors used in the search criteria in the title or abstract and freely available on the internet were selected. Studies that did not meet the inclusion criteria were not selected, as were monographs, dissertations and other course completion papers. Results and discussion: after the study selection stages, only 11 articles were selected. The results of the analysis showed that self-medication is a common practice during pregnancy and most women are unaware of the possible consequences of using medications without a prescription or professional guidance. It was highlighted that the pharmacist is the professional qualified to be part of the multidisciplinary team in monitoring and guiding pregnant women, providing advice to prevent the inappropriate use of medications, carrying out educational actions during dispensing and exercising strict surveillance over the prescribed drug therapy. Conclusion: the pharmacist can play a broad role in guiding pregnant women regarding the use of medications, both in dispensing and in awareness campaigns, playing the role of an educational agent to prevent self-medication.